A Comparison of the Efficacy of Acupuncture and Hypnotherapy in Patients With Migraine. Issue 4 (2nd October 2018) - Tastan, Kenan; Ozer Disci, Ozlem; Set, Turan
Abstract: This study investigated the effect of acupuncture, hypnotherapy, and pharmacotherapy in migraine treatments among 90 patients. They were divided into 3 groups of 30 persons each. Group 1, Group 2, and Group 3 were treated with acupuncture, hypnotherapy, and pharmacotherapy, respectively. Changes in the visual analog scale (VAS) and Migraine Disability Assessment (MIDAS) scores from baseline were monitored. Reductions in the percentages of the VAS and MIDAS scores at the end of the third month were significantly higher in the acupuncture and hypnotherapy groups than those of the pharmacotherapy group ( p < .01). Acupuncture and hypnotherapy can be developed as treatment options alone as an equivalent to conventional treatment.